The Involvement of Long Non-Coding RNAs in Glioma: From Early Detection to Immunotherapy - Wu, Xiaoben; Yang, Lei; Wang, Jing; Hao, Yingying; Wang, Changyin; Lu, Zhiming (Frontiers in Immunology, 2022)
Glioma is a brain tumor that arises in the central nervous system and is categorized according to histology and molecular genetic characteristics. Long non-coding RNAs (lncRNAs) are RNAs longer than 200 nucleotides in length and have been shown to influence carcinogenesis and progression and confer treatment resistance on glioma cells. Long non-coding RNAs promote cell proliferation, migration, EMT, and invasion in glioma cells. Various significant advancements in transcriptomic profiling studies have enabled the identification of immune-related long non-coding RNAs as immune cell-specific gene expression regulators that mediates both stimulatory and suppressive immune responses, implying lncRNAs as potential candidates for improving immunotherapy efficacy against tumors and due to the lack of different diagnostic and treatments for glioma, lncRNAs are considered as potential candidates to be used as future diagnostic, prognostic biomarker and treatment tools for glioma. This review’s primary purpose is to concentrate on the role of long non-coding RNAs in early glioma identification, treatment, and immunotherapy.